ACENG’S UNACCEPTABLE APOLOGY: AN INTERDISCIPLINARY CRITICAL DISCOURSE ANALYSIS - Muhamad Ahsanu (University of Muhammadiyah Purwokerto, 2014)
This paper is aimed at analyzing the apology of the then regent of Garut regency, Aceng, in relation to his brief marital case from interdisciplinary critical discourse analysis (CDA). These cover Speech acts, Narra-tive analysis, sociolinguistic considerations, ideologies and hegemonies. All of them are presented succes-sively to support one another to reach a comprehensive perspective on Aceng‟s phenomenal case. Based on the analysis, it is found that Aceng‟s apology is not effective, it is contra productive. In terms of sociolin-guistic considerations, Aceng‟s apology is against the common shared norms as it is not coming from his heart (insincerity). In terms of ideology, it is clear that marriage was considered to be a sacred thing to do and therefore should be kept (ignored by Aceng), whereas divorcing is hardly acceptable in whatsoever rea-sons. In terms of hegemonies, it is also clear that the powerful dominates the weak, implying that Aceng‟s power was wrongly exercised. Keywords: Apology, Interdisciplinary Discourse Analysis